Role of Resistance to Innovation, Lack of Intercultural Communication, and Student Interest on the Student Demotivation Results Towards the English Education System - Wang, Jin; Pan, Lei (Frontiers in Psychology, 2022)
Recently, second-language learning success depends upon the students' interest and motivation by adopting innovations that require regulators' and new researchers' emphasis. Hence, this article explores the role of resistance to innovation, lack of intercultural communication, and students' interest on the students' demotivation. The article also examines the mediating role of students' demotivation among resistance to innovation, lack of intercultural communication, lack of students' interest, and failure of the English education system in China. This study has gathered the data using survey questionnaires and analyzed the collected data using smart-PLS. The results exposed that the resistance to innovation, lack of intercultural communication, and students' interest have a significant and positive linkage with students' demotivation. The findings also indicated that students' demotivation significantly mediates among resistance to innovation, lack of intercultural communication, lack of students' interest, and failure of the English education system in China. This study guides the policymakers to develop the policies related to improving the English education system in China using innovation that enhances students' interest and motivation. JEL Classifications O31, O32, H75.